The Refugee ritual: Sopron students in Canada - Madokoro, Laura (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractIn the power politics of international migration, the relationship between migrants and the states that receive them are inherently uneven. This is particularly true of the international refugee regime and the manner in which refugees have been identified and resettled in the postwar period. This paper traces the journey of 200 student refugees from Sopron University in Hungary to the University of British Columbia in 1956, following the failure of the Hungarian Revolution. It argues that the manner in which the Sopron students were selected and then settled in Canada assumed ritualistic characteristics with which the federal government attempted to shape their identity and normalize their entry into Canadian society. Tracing the Sopron students’ refugee experience beginning with their flight from Hungary to their graduation from the University of British Columbia, this paper identifies four components to the refugee ritual: selection, movement, settlement and commemoration and argues that because the Sopron forestry students migrated as a group, they experienced the ritual experience to a far greater degree than other student refugees in Canada.